Sustainable Bee-keeping through Farmers FIRST Project interventions in Nainital district of Uttarakhand - Kashyap, S K; Kholiya, Monika (Indian Farming, 2022)
There is enormous potential for bee-keeping in the country. However, due to lack of improved standardized equipments and scientific knowledge, bee-keeping is not being practiced by the bee-keepers serving as one of the major reasons behind low production of honey. In Uttarakhand, farmers use traditional practices for bee-keeping which gives them less economic benefits. In order to obtain high output from bee-keeping, it is necessary for the bee-keepers to use modern technologies and scientific knowledge, participate inthe training and other capacity building programmes. As per the objective, Farmers FIRST Project transferred the improved technologies among the bee-keeping farmers in Jeoli village, trained them to use scientific methods of bee-keeping and made them capable to use honey processing unit and other related equipments which eventually led to alleviate their income and standard of living. Seeing the benefits of bee-keepers, other farmers in the village also have taken up beekeeping as an enterprise to generate additional income. This intervention has helped the bee-keepers to lead sustainable bee-keeping in Jeoli village of Uttarakhandstate.